IDENTIFIKASI PERILAKU MANIPULASI TANTRUM (STUDI DESKRIPTIF PADA ANAK DI KB-TK ISLAM HIDAYATULLAH SEMARANG) - Puspitasari, Dwi (Indonesian Journal of Early Childhood Education Studies, 2012)
Behavioral manipulation often occurs in children who are less full attention from the parents. The manipulation was done by children not because ofÂ  the accident, the child usually has a purpose for doing so, for example, to get the attention of his parents or try the extent to which the patience of parents. Understanding child development not only makes us know what is going to happen in a certain stage of the childâs life, but also help us understand how children think and understand yourself. As for the purpose of this research is: 1) find out the factors that cause the childexperienced a tantrum at KB-TK Hidayatullah Semarang. 2) Knowing the shape or style tantrum manipulation performed by children at KB-TK Hidayatullah Semarang. Based on the results of this research was that tantrum behavior manipulation occurs due to a problem that is being faced by parents that their impact on children, parenting parents overindulge children or too curb child and parenting are dif ferent between the two different people and forms of behaviour manipulation of the tantrum was upset, crying, yelling, hitting. For educators and parents should betterunderstand the childâs character and provide in accordance with the requirements needed by the child. The limitations in this study is time management with the subjects of research.smart method ofÂ  learning the model-based learning solution to maximize the potential ofÂ  multiple Intelligence itself is ef fective in early childhood. Multiple intelligencesinclude spatial, linguistic, interpersonal, musical, natural, body / KINESTHETIC, intrapersonal, and logicalmathematical. This study is also effective to improve teacher performance, so it can be said to be smart method of learning is an effective solution to improve the quality of learning.